Crypto-Currency: Investing in New Models to Advance the Study of Cryptosporidium Infection and Immunity - Marzook, N. Bishara; Sateriale, Adam (Frontiers in Cellular and Infection Microbiology, 2020)
Cryptosporidiosis is a leading cause of diarrheal disease and an important contributor to global morbidity and mortality. Although the brunt of disease burden is felt by children in developing countries, Cryptosporidium is a ubiquitous intestinal parasite with frequent outbreaks around the world. There are no consistently effective treatments for cryptosporidiosis and the research to drive new developments has stagnated, largely due to a lack of efficient in vivo and in vitro models. Fortunately, these research barriers have started to fall. In this review, we highlight two recent advances aiding this process: A tractable mouse model for Cryptosporidium infection and stem cell-based in vitro culture systems that mimic the complexity of the host intestine. These models are paving the way for researchers to investigate Cryptosporidium infection and host immunity down to a molecular level. We believe that wise investments made to adopt and develop these new models will reap benefits not only for the Cryptosporidium community but also for the intestinal immunology field at large.